Does sex matter? Longitudinal course and predictors of knowledge about immunosuppressant medication in patients after kidney transplantation: a KTx360° substudy - Nöhre, Mariel; Meier, Deborah; Talamo, Julia; Tegtbur, Uwe; Pape, Lars; Schiffer, Mario; de Zwaan, Martina (Frontiers in Transplantation, 2026)
BackgroundTo ensure long term graft and patient survival after kidney transplantation, the correct intake of the immunosuppressive medication is mandatory. To correctly administer the medication, specific knowledge is required. While the significance of adherence has been recognized by many, the potential adverse effects of insufficient knowledge levels—often associated with poor health literacy—have been overlooked for a long time; therefore, little is known about sex-specific differences and other predictors of knowledge in this patient group.MethodsWe analyzed the longitudinal course of the self-developed and previously successfully applied knowledge test in kidney transplant recipients participating in the KTx360° trial over a period of up to three years. The patients participated in a multidisciplinary aftercare program that included case management, psychosocial assessments and interventions, as well as exercise assessments and interventions, supported by telemedicine. We aimed to identify potential baseline predictors of knowledge trajectories, with a specific focus on sex-specific differences.ResultsThe analysis sample, which consisted of participants with at least one valid measurement on the knowledge test, included 783 adult patients (41.6% women) with a mean age of 52.3 years (SD 13.6). Knowledge levels improved significantly over the period of the KTx360° trial. Especially younger male participants and men not living in a partnership showed an increase in knowledge levels.ConclusionsOver the period of the KTx360° trial we observed an increase in knowledge, mainly in patients with below-average baseline knowledge levels. While some improvements might be due to the catch-up effect, other changes suggest a different response to the same stimulus. In sex-specific analyses, we found higher knowledge levels in female participants at the start, but sex did not impact the progression of knowledge levels. Since there was no control group, it is not possible to determine the program's effect on knowledge levels.